2012
DOI: 10.1103/physrevb.86.134114
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of NiCxand NiNx(x=0toet al.

Abstract: First-principles calculations have been performed for a variety of Ni 3 X (X = C, N) phases, as well as for NiX y (y = 0 to 1 3 ) solid solutions to clarify the persistent controversy regarding its magnetic state. The calculations show that the solid solution phases based on hexagonal-close-packed (hcp or ε-) Ni have relatively high stability for X concentrations greater than about 0.1 whereas the face-centered-cubic (fcc or γ -) Ni phases are favored for smaller X concentration. Hence, during carburization or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 47 publications
(77 reference statements)
2
29
0
Order By: Relevance
“…While I-M 4 N is magnetic, chemical changes II-Ni 4 N 1AEx (with x $ 0.03) cause local distortion and the defective phases becomes non-magnetic. 41 That is also the case for II-Ni 4 N.…”
Section: -13mentioning
confidence: 99%
See 3 more Smart Citations
“…While I-M 4 N is magnetic, chemical changes II-Ni 4 N 1AEx (with x $ 0.03) cause local distortion and the defective phases becomes non-magnetic. 41 That is also the case for II-Ni 4 N.…”
Section: -13mentioning
confidence: 99%
“…The formation energy (DE) of a metal nitride with the formula, M 4 N, M ¼ Sc to Cu with respect to the elemental 3d transition metal M and the N 2 molecule can be described as: 41,54,55 …”
Section: Formation Energymentioning
confidence: 99%
See 2 more Smart Citations
“…But studies on NieC system are quite limited. Fang and Sluiter have studied the structural and magnetic properties of Ni 3 C phases and hcp-NiC y solid solution using first-principles calculations [11] and the results showed that the nonmagnetic solution was the most stable for both hcp-Ni 3 N and 3ReNi 3 C, and the hcp-NiX y solid solutions remained ferromagnetic up to y~0. 20.…”
Section: Introductionmentioning
confidence: 98%